Voting Behaviour in Assembly Election of Varanasi: A Geographical Analysis - Kumar, Rohit; Singh, Arun K. (National Geographical Journal of India, 2022)
This study focuses on voting behaviour of the electorates in two consecutive assembly elections of Varanasi district. Mapping the voting behaviour pattern is one of the great significance for an electoral geographer as it depicts the level of political awareness, consciousness and socio-economic development of that area. Voting behaviour is not confined to the examination of voting statistics, records and computation of electoral shifts and swings, it also involves an analysis of individual’s psychological processes (perception, emotion and motivation) and their influence on political decision. In this paper the main objective is to examine the voting behaviour pattern and to study the factors responsible for the spatial changes in voting pattern as well as voting behaviour from one constituency to another in the two consecutive assembly elections of 2012 and 2017.The study is based on secondary data collected from the Election Commission of India and other published and unpublished sources